EFFECT OF COW MANURE AND PHOSPHATE FERTILIZER ON GROWTH AND PHYSIOLOGICAL CHARACTERISTIC OF AZOLLA (AZOLLA MICROPHYLLA) - Banharn, Sirasatiyakorn; Janthakam, Sawinee (PSRU Journal of Science and Technology, 2025)
The objective of this research was to study the effects of cow manure and phosphate fertilizer on growth, morphological and physiological characteristics in terms of total chlorophyll content, protein content and the amount of Cyanobacteria (Anabaena azollae) living in Azolla microphylla by growing Azolla in tap water (Control; T1) compared with 4 fertilizer formulas: cow manure fertilizer 500 grams (T2), cow manure mixed with soil at a ratio of 500 grams per 2 kilograms (T3), rock phosphate (P2O5) 30 grams (T4), and monopotassium phosphate fertilizer (KH2PO4) 30 grams (T5). Experimental data were collected at 30 days. From the results, it was found that Azolla fed with rock phosphate had the highest shoot dry weight and root number but Azolla cultivated with cow manure alone had the highest relative growth rate, total chlorophyll content and the amount of Cyanobacteria. But it could be seen that Azolla fed with cow manure and monopotassium phosphate had the highest protein content. The information in this study can be use as basic information in Azolla cultivation and further apply in agriculture.